(untitled) (Kinesiology, 2023)
This study aimed to analyze the changes in match physical performance in professional soccer players after sustaining a hamstring injury, which was categorized based on injury severity. Seventy-two hamstring injuries involving sixty-four professional soccer players from the Spanish LaLiga™ were considered for this study. All injuries were classified according to their severity as moderate (resulting in eight to 28 missed days) and major (resulting in more than 28 missed days). Mediacoach video-tracking system collected time and external load variables and subsequently compared them between the pre-injury and return-to-play periods. The analyzed variables included distance covered at different velocities (i.e., total distance, at 18-21 km.h−1, at 21-24 km.h−1, and at more than 24 km.h-1), the number of sprints, accelerations, decelerations, and high metabolic load distance (HMLD). The results showed that players with both the moderate and major injuries played fewer minutes after injury (p<.001 to p<.05) and experienced a decrease in maximum speed (p<.01 to p<.05), covering less total distance (p<.05) and exhibiting a decrease (p<.05) in average speed (only observed in players with major injuries). Additionally, moderately injured players experienced a reduction in the number of maximum accelerations (p<.05) and decelerations (p<.05), high metabolic load distance/min (p<.05), and average accelerations (p<.05). Furthermore, a significant reduction in the magnitude of maximum decelerations was observed in players with major injuries (p<.05). These findings highlight the importance of implementing strategies that enable the attainment of initial levels of high-intensity actions and maximum speed in reconditioning programs following hamstring injuries. Key words: physical conditioning, thigh muscles, external load, playing time, video tracking, return to play, football